2010
DOI: 10.2106/jbjs.j.00214
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Osteochondral Mosaicplasty for Osteochondritis Dissecans of the Elbow in Teenage Athletes

Abstract: DISCLOSURE:The authors did not receive any outside funding or grants in support of their research for or preparation of this work. Neither they nor a member of their immediate families received payments or other benefits or a commitment or agreement to provide such benefits from a commercial entity. 91-A, pp. 235991-A, pp. -66, October 2009 ABSTRACT FROM THE ORIGINAL ARTICLE BACKGROUND: Although autologous osteochondral mosaicplasty is widely used as a procedure for osteochondritis dissecans lesions, the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(79 citation statements)
references
References 15 publications
3
76
0
Order By: Relevance
“…Shimada et al 4) reported excellent results in 80% of their patients, and Iwasaki et al 6) showed that 94.4% of their patients had good or excellent outcomes and 88.9% returned to sports activities. Neither group mentioned the use of the elbow brace in their reports 4,6) . Lyons et al 2) reported better clinical outcomes in adolescent athletes, with a 100% return rate to former sports activities.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Shimada et al 4) reported excellent results in 80% of their patients, and Iwasaki et al 6) showed that 94.4% of their patients had good or excellent outcomes and 88.9% returned to sports activities. Neither group mentioned the use of the elbow brace in their reports 4,6) . Lyons et al 2) reported better clinical outcomes in adolescent athletes, with a 100% return rate to former sports activities.…”
Section: Discussionmentioning
confidence: 98%
“…There are many reports of good results of osteochondral grafting for OCD of the elbow [4][5][6] . Shimada et al 4) reported excellent results in 80% of their patients, and Iwasaki et al 6) showed that 94.4% of their patients had good or excellent outcomes and 88.9% returned to sports activities.…”
Section: Discussionmentioning
confidence: 99%
“…6 In another study of bone-peg grafting and/ or insertion of a resorbable pin for unstable OCD lesions but attached to the bony bed of the capitellum, 6 of 7 patients achieved bony union and one failed. 5 In studies of osteochondral plug grafting for OCD grade III and IV lesions, the mean TimmermanAndrews score has been reported to improve significantly: from 150 to 180 with 77% of patients able to resume their former level of sport, 10 from 131 to 191 with 90% of patients able to resume their former level of sport, 11 and from 130 to 190 with 91% of patients able to resume their competitive level after a mean of 6.9 months. 12 In our study, the score improved from 163 to 189 with 70% of patients able to resume sport at a competitive level.…”
Section: Discussionmentioning
confidence: 99%
“…When the OCD fragment is not salvageable, autograft osteochondral plugs can be taken from the knee [50][51][52] or harvested from either the fifth or sixth costal-osteochondral junction and implanted [41,53,54]. Most surgeons who perform capitellar OATS more commonly utilize the knee as a source for donor graft due to the familiarity of the anatomy and avoidance of complications associated with iatrogenic injury to the costal pleura.…”
Section: Arthroscopic Managementmentioning
confidence: 99%